Beberapa Isu Pengukuran Konstruk dalam Riset Keperilakuan dan Organisasi - BM. Purwanto, MBA, Ph.D. BM. Purwanto, MBA, Ph.D. (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Surakarta, 2014)
This paper discusses important issues on measurement in behavioral research. It gives guidance to researcher and management scholars to construct measurement in their research. The purpose of this paper is to give awareness to researcher to develop measurement. This paper discusses fundamental issues on measurement such as multidimensional, reflective and formative measurement and item-parcell issues.